A Nonuniform Clustering Routing Algorithm Based on a Virtual Gravitational Potential Field in Underwater Acoustic Sensor Network - Zhang, Wenbo; Wang, Jia; Han, Guangjie; Feng, Yongxin; Tan, Xiaobo (IEEE internet of things journal, 2023)
Due to the harsh deployment environment of the underwater coustic sensor networks (UASNs), a reliable and energy-saving routing algorithm has always been an important challenge and a hot topic. A Nonuniform clustering (NC) algorithm is designed first in which clusters are generated according to different node densities. Based on NC, the backbone of the underwater acoustic sensor network is formed in UASNs. To guarantee the reliability of data transmission of the backbone network, an NC routing algorithm based on a virtual gravitational potential field (NC_RVGPF) is proposed. This algorithm: 1) establishes a virtual gravitational potential field model to allow data transmission by 3-D underwater nodes; 2) designs the virtual gravitational potential energy by combining the transmission distance between the nodes, the residual energy of the nodes, and other parameters; and 3) selects the path of the highest average potential energy as being the optimal path of data transmission. The simulation results show that compared with the classical routing algorithm, the NC_RVGPF algorithm has higher transmission efficiency, less energy consumption, and can more effectively extend the network's lifetime.